Factors associated with late booking of antenatal care among pregnant women during Covid-19 pandemic - Lim, Poh ying; Nasir, Faizah; Lee, Khuan; Ahmad, Norliza (Malaysian Public Health Physicians' Association, 2023)
The prevalence of late antenatal care (ANC) booking in Malaysia is higher than the target set by the Ministry of Health (20%). First ANC is suggested to be conducted within 12 gestation weeks. This study aims to investigate the prevalence and factors of late booking of ANC among pregnant women in Sepang, Selangor. A cross-sectional study using a self-administered questionnaire on 492 pregnant women in the first, second, and third trimesters was conducted randomly at government health clinics. The prevalence of late ANC booking was 27.6% (136). Multiple logistic regression showed that poor knowledge (AOR = 1.604, 95% CI:1.022,2.517, P-value = 0.040), higher parity (AOR = 1.225, 95% CI:1.003,1.495, P-value = 0.046), previous experience of spontaneous vaginal delivery (SVD, AOR = 2.855, 95% CI:1.227,6.645, P-value = 0.015) and did not have experience on delivery (AOR = 2.906, 95% CI:1.147,7.364, P-value = 0.025) associated with late ANC booking. The prevalence of late ANC booking in this study was higher than MOH targeted, therefore it is suggested to devise the appropriate program to improve knowledge and awareness of the targeted high-risk population.